Теоретичні аспекти корпоративної культури в організації - Агєєва, Ірина Вікторівна; Агеева, Ирина Викторовна; Ahieieva, Iryna (Мелітополь: ТДАТУ, 2018)
UK: У роботі досліджено теоретичні підходи до аспектів управління корпоративною культурою, узагальнено теоретичні уявлення вітчизняних і зарубіжних вчених про сутність даного поняття. Проаналізовано існуючі підходи до трактування поняття «корпоративна культура». Визначено особливості вітчизняних підходів до поняття "корпоративна культура". EN: In modern conditions, the efficiency of enterprises is determined by the level of development of their cor-porate culture. Each organization has its own special culture, a harmonious relationship between its employees, the ethics of personnel behavior, which determines its image and reputation. Therefore, in recent years in the scientific and business circles there has been a rapid growth of attention to the notion of "corporate culture". Corporate culture can play an important role in enhancing the level of engagement of employees, using intelligent technology and ensuring the welfare of workers. And this will lead the organization to positive changes. It is under these conditions that the cor-porate culture gets special attention.
Theoretical aspects of corporate culture in organization
Keywords: організація; корпоративна культура; організаційна культура; цінності; organization; corporate culture; organizational culture; value